Southey, Macaulay and the Idea of a Picturesque History - Wohlgemut, Esther (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractThe intersection of history and literature in late-eighteenth- and early-nineteenth-century Britain has received a great deal of attention lately, and critics like Mark Phillips and Karen O’Brien have drawn attention to the ways in which Romantic historians such as Thomas Babington Macaulay drew on literary techniques and genres to create evocative and spectacular histories. But the same milieu that produced Macaulay also produced Robert Southey, whose much less discussed Sir Thomas More; or, Colloquies on the Progress and Prospects of Society (1829) foregrounds another affective history in the period, one dependent on a generic intersection between history and travel writing. Part picturesque tour, part social history, and part ghost story, Colloquies figured prominently in the larger cultural debate over the question of reform in Britain, and it offers an important counterpoint to Romantic histories such as Macaulay’s. Combining history with travel writing and dream vision, Southey exploits their convergence to create a different kind of spectacular history. This generic convergence—in particular, Southey’s use of the picturesque—is central to Macaulay’s indictment of Southey’s historical methodology in his review of Colloquies. The Southey-Macaulay contest over the idea of a picturesque history is part of a larger debate that was taking place about the status of history in post-Waterloo Britain.